HUBUNGAN KANDUNGAN BAHAN ORGANIK TANAH DENGAN BERAT ISI, POROSITAS DAN LAJU INFILTRASI PADA PERKEBUNAN SALAK DI KECAMATAN PURWOSARI, KABUPATEN PASURUAN - Danny Dwi Saputra; Amir Rakhim Putrantyo; Zaenal Kusuma (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Poor quality of agricultural soil is characterized by low soil organic matter (OM) content, high bulk density, low porosity, and low infiltration. One of efforts to improve soil quality is by adding OM from biomass prunings. Aim of this study was to test the effectiveness of adding OM to the increase of soil organic carbon (SOC) and its relationship with soil bulk density, porosity and infiltration. This study was conducted at Salak (Salacca zalacca Gaertner Voss) plantation owned by a smallholder farmer in Pasuruan District, East Java. Measurements were done at three different treatments of organic material and condition, i.e. at litter stackline (addition of OM), between the Salak plant (without OM addition) and pathway (farmer traffic line) on two age groups of Salak (10 and 20 years) with 3 replications. Soil samples were collected from three f soil profile depths, 00-10, 10-20 and 20-30 cm. Parameters measured were soil organic carbon content, bulk density, particle density, porosity and infiltration rate. Results showed that addition of organic matter from Salak biomass effectively increased the SOC content. However, the increase of SOC content only had positive effects on soil bulk density, porosity, and infiltration rate at the 10 years old group of Salak plantation.